Convex games versus clan games - Rodica Branzei; Dinko Dimitrov; Stef Tijs (Bielefeld University, Institute of Mathematical Economics (IMW), 2006)
In this paper we provide characterizations of convex games and total clan games by using properties of their corresponding marginal games. We show that a 'dualize and restrict' procedure transforms total clan games with zero worth for the clan into monotonic convex games. Furthermore, each monotonic convex game generates a total clan game with zero worth for the clan by a 'dualize and extend' procedure. These procedures are also useful for relating core elements and elements of the Weber set of the corresponding games.
urn:nbn:de:hbz:361-9098
Keywords: C71; 330; Convex games; Core; Dual games; Marginal games; Total clan games; Weber set; Kooperatives Spiel; Core; Koalition; Spieltheorie